The reality of partnership: formal collaborations between law enforcement and community corrections agencies in Pennsylvania - Kim, Bitna (Policing and society, 2018)
As is the case in the UK, formal police–community corrections partnerships in the US have existed since the 1990s. However, unlike the UK where parliamentary developments and subsequent policy initiatives have provided a context in which criminal justice agencies formally work together, police–probation/parole partnerships in the US have experienced relatively little formalisation, with most extant partnerships existing informally based principally on interpersonal relations between individual police and corrections agency members. Relevant to research in the UK [Mawby, R.C., Crawley, P., and Wright, A., 2007. Beyond ‘polibation’ and towards ‘prisi-polibation’? Joint agency offender management in the context of the street crime initiative. International journal of police science & management, 9 (2), 122–134; Mawby, R.C. and Worrall, A., 2004. ‘Polibation’ revisited: policing, probation and prolific offender projects. International journal of police science and management, 6 (2), 63–73; Mawby, R.C. and Worrall, A., 2011. ‘They were very threatening about do-gooding bastards’: probation’s changing relationships with the police and prison services in England and Wales. European journal of probation, 3 (3), 78–94; Nash, M., 2008. Exit the polibation officer? Decoupling police and probation. International journal of police science and management, 10 (3), 302–312; Nash, M. and Walker, L., 2009. MAPPA – is closer collaboration really the key to effectiveness? Policing, 3 (2), 172–180; Wood, J. and Kemshall, H., 2007. The operation and experience of Multi-Agency Public Protection Arrangements (MAPPA). London: Home Office], the current study explores the patterns and characteristics of formal partnerships and the perceptions of police chiefs and probation/parole chiefs in a US state concerning experiences with partnering agencies, benefits, and problems. Findings are compared with research findings in the UK and Canada.